The Cold War and After : History, Theory, and the Logic of International Politics - Trachtenberg, Marc, 1946- (Book collections on Project MUSE., 2012)
What makes for war or for a stable international system? Are there general principles that should govern foreign policy? In The Cold War and After, Marc Trachtenberg, a leading historian of international relations, explores how historical work can throw light on these questions. The essays in this book deal with specific problems--with such matters as nuclear strategy and U.S.-European relations. But Trachtenberg's main goal is to show how in practice a certain type of scholarly work can be done. He demonstrates how, in studying international politics, the conceptual and empirical sides of the analysis can be made to conncect with each other, and how historical, theoretical, and even policy issues can be tied together in an intellectually respectable way.